Ant diversity in Brazilian tropical dry forests across multiple vegetation domains - Luciana Figueiredo Silva; Rayana Mello Souza; Ricardo R C Solar; Frederico de Siqueira Neves (Environmental Research Letters, 2017)
Understanding the environmental drivers of biodiversity persistence and community organization in natural ecosystems is of great importance for planning the conservation of those ecosystems. This comprehension is even more important in severely threatened ecosystems. In this context, we analyzed ant communities in tropical dry forests (TDFs) in Brazil. These forests are embedded within other biomes, such as Cerrado and Caatinga. In this study, we asked whether (i) ant species richness and composition changes between TDFs within different vegetation domains; (ii) whether ant species richness and β -diversity increase north-to-south, possibly related to changes in tree richness and tree density; and (iii) species replacement contributes relatively more to β -diversity than does nestedness. We found that species composition is unique to each TDF within different biomes, and that species richness and β -diversity differ among the vegetation domains, being smaller in the Caatinga. We also found that replacement contributes most to β -diversity, although this contribution is lower in Caatinga than in Cerrado. We show that regional context is the main driver of species diversity, which is likely to be driven by both historical and ecological mechanisms. By analyzing large spatial scale variation in TDF environmental characteristics, we were able to evaluate how ant diversity changes along an environmental gradient. The high levels of species replacement and unique species composition of each region indicates that, to fully conserve TDFs, we need to have various conservation areas distributed across the entire range of vegetation domains in which these forests can be found. Thus, we demonstrate that a landscape-wise planning is urgent and necessary in order to preserve tropical dry forests.